2021
DOI: 10.1093/nar/gkab756
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like kinase 1 (Plk1) regulates DNA replication origin firing and interacts with Rif1 in Xenopus

Abstract: The activation of eukaryotic DNA replication origins needs to be strictly controlled at multiple steps in order to faithfully duplicate the genome and to maintain its stability. How the checkpoint recovery and adaptation protein Polo-like kinase 1 (Plk1) regulates the firing of replication origins during non-challenged S phase remained an open question. Using DNA fiber analysis, we show that immunodepletion of Plk1 in the Xenopus in vitro system decreases replication fork density and initiation frequency. Nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 80 publications
3
34
1
Order By: Relevance
“…Recently, PLK1 was shown in an in vitro system to be essential in regulating the spatio-temporal replication program by interacting with several origin firing factors (i.e. RIF1, TRESLIN; TopBP1), and the immuno-depletion of PLK1 reduced the number of replication forks and origins firing ( 35 ), giving additional proof of the PLK1’s role also in S-phase.…”
Section: Plk1 and Its Role In Genomic Stabilitymentioning
confidence: 99%
“…Recently, PLK1 was shown in an in vitro system to be essential in regulating the spatio-temporal replication program by interacting with several origin firing factors (i.e. RIF1, TRESLIN; TopBP1), and the immuno-depletion of PLK1 reduced the number of replication forks and origins firing ( 35 ), giving additional proof of the PLK1’s role also in S-phase.…”
Section: Plk1 and Its Role In Genomic Stabilitymentioning
confidence: 99%
“…In human cells, Rif1-phosphorylation is also dependent on CDK1 [ 69 ]. In Xenopus egg extract, which mimics the first S phase after fertilization, depletion of Rif1 or Rif1-CTD (C-terminal domain that contains PP1-binding site) results in less PP1 on chromatin and a reduced rate of MCM-phosphorylation [ 69 , 70 ]. This suggests that Rif1 has the potential to regulate replication in the earliest stages of vertebrate development.…”
Section: Rif1 Activity Is Regulated During Developmentmentioning
confidence: 99%
“…This suggests that Rif1 has the potential to regulate replication in the earliest stages of vertebrate development. Interestingly, in Xenopus, Polo-like kinase 1 (Plk1) can phosphorylate Rif1 near its PP1-binding site, suggesting that Rif1 is the target of multiple cell-cycle-regulated kinases [ 70 ].…”
Section: Rif1 Activity Is Regulated During Developmentmentioning
confidence: 99%
“…Independently of MCM phosphorylation, DDK activity has been shown to promote the formation of Treslin:MTBP:TopBP1 complex that supports replication initiation ( Figure 2 iv,v). The DDK substrate mediating this increased complex formation remains to be fully characterised as both Treslin and MTBP demonstrate a DDK-dependent mobility shift [ 5 , 70 ]. Furthermore, it was shown that DDK-dependent phosphorylation of Treslin is required to facilitate the conserved CDK-mediated phosphorylation of Treslin that is required for interaction with TopBP1 [ 5 ].…”
Section: Replication Origin Selection and Activation: Ddk-mediated Ph...mentioning
confidence: 99%